Refinement of a meaning-centered counseling program for Chinese patients with advanced cancer: integrating cultural adaptation and implementation science approaches - Florence Lui; Qingyi Zhang; George Chengxi Bao; Bharat Narang; Ruo Yan Chen; Yunshan Niu; Jennifer Leng; William Breitbart (BMC Health Services Research)
Abstract Background This mixed methods study identified needed refinements to a telehealth-delivered cultural and linguistic adaptation of Meaning-Centered Psychotherapy for Chinese patients with advanced cancer (MCP-Ch) to enhance acceptability, comprehensibility, and implementation of the intervention in usual care settings, guided by the Ecological Validity Model (EVM) and the Practical, Robust Implementation and Sustainability Model (PRISM). Methods Fifteen purposively sampled mental health professionals who work with Chinese cancer patients completed surveys providing Likert-scale ratings on acceptability and comprehensibility of MCP-Ch content (guided by the EVM) and pre-implementation factors (guided by PRISM), followed by semi-structured interviews. Survey data were descriptively summarized and linked to qualitative interview data. Three analysts independently coded the transcripts according to EVM and PRISM domains; discrepancies were resolved through discussion and consensus. Results Quantitative findings showed high appropriateness and relevance of MCP-Ch across five EVM domains of Language, Metaphors/Stories, Goals, Content, and Concepts. Qualitative analysis yielded 23 inductive codes under the seven EVM domains: (1) Language (3 subcodes), (2) Persons (2 subcodes), (3) Metaphors/Stories (2 subcodes), (4) Methods (8 subcodes), (5) Content (2 subcodes), (6) Goals (4 subcodes), and (7) Concepts (2 subcodes). Themes based on PRISM included (1) Intervention characteristics (organizational perspective, 7 subcodes; and patient perspective, 6 subcodes) (2) External environment (2 subcodes), (3) Implementation and sustainability infrastructure (4 subcodes), and (4) Recipients (organizational characteristics, 5 subcodes; and patient characteristics, 4 subcodes). Conclusion Recommendations for next steps include increasing the MCP-Ch protocol’s flexibility and adaptability to allow interventionists to flexibly tailor MCP-Ch material to meet patients’ individual needs, simplifying content to improve comprehension and acceptability, providing additional training to Chinese-serving providers to increase adoption and sustainability, and considering interpreter-assisted delivery to increase access. Findings yielded important information to maximize cultural relevance as well as the implementation and sustainability potential of MCP-Ch in real-world settings.